2021
DOI: 10.1039/d0sm01858a
|View full text |Cite
|
Sign up to set email alerts
|

Lateral motion of a droplet impacting on a wettability-patterned surface: numerical and theoretical studies

Abstract: A general parameter of effective retraction area has been established to connect the wettability patterns with droplet lateral motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…Zhao et al (2019) and Chu et al (2020) further investigated the effect of impact position on the lateral transport distance. Russo et al (2020) and Zhang, Wu & Lin (2021) also observed similar phenomena in numerical simulations, and the effect of multiple parameters on the droplet motion was systematically investigated. The dominating factor of droplet lateral motion is the presence of asymmetric forces, which are induced by a hydrophilic stripe arranged on one side of the impact point (Zhao et al 2019(Zhao et al , 2021.…”
Section: Introductionmentioning
confidence: 68%
“…Zhao et al (2019) and Chu et al (2020) further investigated the effect of impact position on the lateral transport distance. Russo et al (2020) and Zhang, Wu & Lin (2021) also observed similar phenomena in numerical simulations, and the effect of multiple parameters on the droplet motion was systematically investigated. The dominating factor of droplet lateral motion is the presence of asymmetric forces, which are induced by a hydrophilic stripe arranged on one side of the impact point (Zhao et al 2019(Zhao et al , 2021.…”
Section: Introductionmentioning
confidence: 68%
“…Regulating surface wettability has proven to be an effective method for precisely controlling the droplet dynamic behaviors 34 , 35 . For example, the gyrating and dancing of droplets are realized through heterogeneous surface wettability regulation 33 , and droplet directional bouncing and materials transportation 36 39 have been achieved by constructing patterned-wettability surface where the droplet lateral velocity is found to be related to the surface area of a geometric region 36 , 37 . During these rebounding processes, however, satellite drops may still be produced due to Plateau–Rayleigh instability.…”
Section: Introductionmentioning
confidence: 99%
“…Adhesion and pinning forces of droplets to surfaces govern their motion and dynamics. , These transport phenomena are highly important for controlling fluids at interfaces, collection and removal, or accumulation of liquids at specific places . These are especially relevant to heat transfer across interfaces, inkjet printing and surface patterning, , and collecting condensed water in applications such as fog and dew harvesting .…”
mentioning
confidence: 99%
“…These are especially relevant to heat transfer across interfaces, inkjet printing and surface patterning, , and collecting condensed water in applications such as fog and dew harvesting . In addition, adhesion forces also govern the dynamics of fundamental wetting phenomena, including droplet impact and bouncing, , condensation and evaporation, and droplet sliding …”
mentioning
confidence: 99%
See 1 more Smart Citation